2012
DOI: 10.1186/1752-1947-6-356
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic pulmonary pseudocyst with hemopneumothorax following blunt chest trauma: a case report

Abstract: IntroductionPost-traumatic pulmonary pseudocyst is an uncommon cavitary lesion of the lung and develops after blunt chest trauma and even more rarely following penetrating injuries. It is generally seen in young adults presenting with cough, chest pain, hemoptysis, and dyspnea. Post-traumatic pulmonary pseudocyst should be included in the differential diagnosis of cavitary pulmonary lesions. We describe the case of a 60-year-old Caucasian Greek woman who sustained traumatic pulmonary pseudocyst with hemopneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…These arise acutely after trauma and typically resolve without intervention. 16 We felt this diagnosis was unlikely given our patient’s lack of recalled trauma.…”
Section: Discussionmentioning
confidence: 92%
“…These arise acutely after trauma and typically resolve without intervention. 16 We felt this diagnosis was unlikely given our patient’s lack of recalled trauma.…”
Section: Discussionmentioning
confidence: 92%
“…Men have more motor vehicle accidents and fall more from a high distance. Therefore, they are reported to be more likely to be affected [ 8 ]. Similarly, in our study, most of the patients were male (n=22, 73.3%).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that traumatic pulmonary pseudocysts are more often seen in children and young adults because of greater compliance of the chest wall permitting larger transmission of force to the parenchyma [4]. Impact velocity and degree of chest wall displacement is thought to alter the type of lesion with high velocity impact causing peripheral lesions while low velocity impact produces central parenchymal and bronchial disruption [5] A series of chest X-rays taken over several days can be used to differentiate traumatic pulmonary pseudocysts from other kinds of cystic or cavitary lesions [6]. The lesions are reported to resolve spontaneously over a period of one to six months [7].…”
Section: Discussionmentioning
confidence: 99%